Twenty key questions in environmental and resource economics - Lucas Bretschger; Karen Pittel (ETH Zurich, CER-ETH - Center of Economic Research, 2019)
Economic and ecological systems are closely interlinked at a global and a regional level, offering a broad variety of challenging research topics in environmental and resource economics. The successful identification of key questions for current and future research supports development of novel theories, empirical applications, and appropriate policy designs. It allows establishing a future-oriented research agenda whose ultimate goal is an efficient, equitable, and sustainable use of natural resources. The paper aims to identify fundamental topics, current trends, and major research gaps to motivate further development of academic work in the field.
Keywords: Q00; Q2; Q3; Q5; 330; environmental and resource economics; survey; key research topics